New Insights Into DAEC and EAEC Pathogenesis and Phylogeny - Meza-Segura, Mario; Zaidi, Mussaret B.; Vera-Ponce de León, Arturo; Moran-Garcia, Nadia; Martinez-Romero, Esperanza; Nataro, James P.; Estrada-Garcia, Teresa (Frontiers in Cellular and Infection Microbiology, 2020)
Diarrheagenic E. coli can be separated into six distinct pathotypes, with enteroaggregative (EAEC) and diffusely-adherent E. coli (DAEC) among the least characterized. To gain additional insights into these two pathotypes we performed whole genome sequencing of ten DAEC, nine EAEC strains, isolated from Mexican children with diarrhea, and one EAEC plus one commensal E. coli strains isolated from an adult with diarrhea and a healthy child, respectively. These genome sequences were compared to 85 E. coli genomes available in public databases. The EAEC and DAEC strains segregated into multiple different clades; however, six clades were heavily or exclusively comprised of EAEC and DAEC strains, suggesting a phylogenetic relationship between these two pathotypes. EAEC strains harbored the typical virulence factors under control of the activator AggR, but also several toxins, bacteriocins, and other virulence factors. DAEC strains harbored several iron-scavenging systems, toxins, adhesins, and complement resistance or Immune system evasion factors that suggest a pathogenic paradigm for this poorly understood pathotype. Several virulence factors for both EAEC and DAEC were associated with clinical presentations, not only suggesting the importance of these factors, but also potentially indicating opportunities for intervention. Our studies provide new insights into two distinct but related diarrheagenic organisms.